2021
DOI: 10.3389/fonc.2021.739660
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Expression and Prognostic Value of the TCP1 Ring Complex in Hepatocellular Carcinoma and Overexpressing Its Subunit 5 Promotes HCC Tumorigenesis

Abstract: T-complex protein-1 ring complex (TRiC), also known as Chaperonin Containing T-complex protein-1 (CCT), is a multisubunit chaperonin required for the folding of nascent proteins. Mounting evidence suggests that TRiC also contributes to the development and progression of tumors, but there are limited studies on pathogenic functions in hepatocellular carcinoma (HCC). We comprehensively evaluated the expression pattern and biological functions of TRiC subunits using The Cancer Genome Atlas and The Human Protein A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Subsequently, we further con rmed the accuracy of the prognostic signature for predicting immunotherapy response using TIDE scores and external immunotherapy data Other investigations have corroborated the important genes involved in signature creation in our work. The proliferation rate, transition through the cell cycle, migration, and invasion were all reduced when CCT5 was knocked down in an HCC cell line, but elevated when CCT5 was overexpressed, as reported by Liu [25] . Shen [26] et al concluded that FLVCR1 was connected with the metabolism of HCC cells and that its overexpression predicted a bad prognosis for HCC patients.…”
Section: Discussionsupporting
confidence: 68%
“…Subsequently, we further con rmed the accuracy of the prognostic signature for predicting immunotherapy response using TIDE scores and external immunotherapy data Other investigations have corroborated the important genes involved in signature creation in our work. The proliferation rate, transition through the cell cycle, migration, and invasion were all reduced when CCT5 was knocked down in an HCC cell line, but elevated when CCT5 was overexpressed, as reported by Liu [25] . Shen [26] et al concluded that FLVCR1 was connected with the metabolism of HCC cells and that its overexpression predicted a bad prognosis for HCC patients.…”
Section: Discussionsupporting
confidence: 68%
“…In our study, CCT2 was highly expressed in 27 tumors, and this was confirmed by IHC results. In other studies, the expression levels of TRiC subunits TCP1, CCT2, CCT 3, CCT 4, CCT 5, CCT 6A, CCT 7, and CCT 8 were significantly upregulated in HCC (14). PAAD, READ, STAD, and UCEC are significantly upregulated in CCT2 expression than in adjacent normal tissues (9,15).…”
Section: Discussionmentioning
confidence: 80%
“…The emergence of drug resistance and limited availability of inhibitors targeting multiple cell cycle modulators pose challenges that impede the ability to halt the uncontrolled growth of cancer, leading to malignancy. Although there are currently no clinically available inhibitors or drugs for CCT, the complex and its subunits have garnered increased attention in the eld of drug development 54,55 . Our study revealed that, among the nine CCT subunits, CCT6A showed the highest level of activation in colon cancer.…”
Section: Discussionmentioning
confidence: 99%